Ilustrasi Buku Masakan Tradisional Khas Sumatera Barat Untuk Anak Usia 9-12 Tahun Dalam Upaya Melestarikan Budaya - Widya Haristin; Ariusmedi Ariusmedi (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the provinces in Indonesia that has a variety of traditional cuisine is West Sumatra. Introducing traditional cuisine to the next generation is one way to maintain culture so that it is not forgotten. This traditional introduction still tends to be passed down through oral traditions from previous generations to the cuisine of their predecessors, usually through communication and people's living habits so that it is less than optimal in the long term. The best way to introduce traditional cuisine to children in the long term is to use reading media. Therefore, a cultural introduction was designed for children aged between 9-12 years in illustration-based book media. The design uses the ADDIE approach (Analysis, Design, Development, Implement, Evaluate). The aim of this book is to broaden children's understanding of traditional West Sumatran cuisine.